Coffee price volatility and intra-household labour supply: Evidence from Viet Nam - Ulrik Beck; Saurabh Singhal; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Volatility in commodity markets poses an acute risk to farmers in developing countries who rely on cash crop agriculture. We combine a time series of international coffee prices with a long-running panel on coffee-growing households in Viet Nam to investigate coping mechanisms employed by farmers in a transitioning economy. We find that households cope with lower coffee prices by increasing wage labour of adults with children and adolescents substituting for adults on the farm and in home production. Account should be taken of this finding in formulating and implementing social protection and inclusive growth policies.
Keywords: Q02; J22; O12; 330; intra-household allocation; commodity prices; income shocks; labour supply